The Influence of Literacy Methods and the Use of Serang Javanese Comics on the Vocabulary Skills of Serang Javanese Class IV of SDN Kubang Apu - Gadis Niyanti Pertiwi; Tatu Hilaliyah; Atin Fatimah (FKIP - Universitas Riau, 2026)
Education plays an important role in improving the quality of learning, particularly through the development of effective learning resources. This study aims to determine the effect of reading literacy methods and the use of Serang Javanese comics on the vocabulary skills of fourth-grade students at SDN Kubang Apu. The research method used was a quasi-experiment with a nonequivalent control group design and a quantitative approach. The research instruments were tested for validity and reliability using SPSS, resulting in 30 valid items from 40 statements, with a reliability value of 0.895. The analysis results showed that the data were normally distributed, linear, free of multicollinearity, and had homogeneous variance. Hypothesis testing proved that the literacy method and the use of Serang Javanese comics had a significant effect on improving students' vocabulary skills (p < 0.05). The average pre-test score of 65.41 increased to 74.66 on the post-test, showing an increase of 9.25 points. The use of comics proved to be effective because the visuals and storyline helped students understand the context of vocabulary more easily and interestingly. Thus, the combination of literacy methods and Serang Javanese comics was able to improve vocabulary skills while strengthening the preservation of regional languages in elementary school environments.